Modelling and analysis of the energy intensity in polyacrylonitrile (PAN) precursor and carbon fibre manufacturing. (20th June 2021) - Dér, Antal; Dilger, Nikolas; Kaluza, Alexander; Creighton, Claudia; Kara, Sami; Varley, Russell; Herrmann, Christoph; Thiede, Sebastian
Abstract: Carbon fibre manufacturing is characterized by a high energy demand due to long processing times and energy intensive thermal processes. Since energy flow related information about the carbon fibre production is rare, lacks in detail and ranges widely, the goal of this paper is to increase the transparency of energy flows in the carbon fibre value chain. To this end, the extended energy value stream methodology was modified and applied on a research scale polyacrylonitrile precursor line and a pilot scale carbon fibre line. The paper takes in a holistic factory understanding when quantifying energy demands and it provides highly-detailed energy related data across the carbon fibre manufacturing process chain. Energy demands are broken down into energy carriers, process steps and peripheral levels of the carbon fibre production system. The results of the paper lay a first valuable step towards a comprehensive life cycle inventory of carbon fibre manufacturing. Furthermore, the high transparency of energy data provides a starting point for future research to increase the energy efficiency of carbon fibre manufacturing. With respect to the high share of the technical building services on the total energy demand, the paper emphasizes the need for an integrated assessment and improvement of the manufacturing process and technical building services.